Kepemimpinan dan Penjaminan Mutu; Peran Kepala Sekolah dalam Menunjang Penjaminan Mutu SMA YP 17 Surabaya - Usman Usman; Mohammad Baihaqi (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2020)
The quality assurance and development of an educational institution depends on the quality of the headmaster as an educational leader. Therefore, the headmaster are required to be more creative, innovative and dynamic in line with changes in society that are increasingly fast and open. This study aims to analyze the role of principal leadership in supporting quality assurance at SMA YP 17 Surabaya. This research is a descriptive qualitative research with a case study approach. From the results of the study it can be concluded that in supporting quality assurance, the leadership of the head of SMA YP 17 Surabaya is supported by the character of strong responsibility, courage in making decisions, and participation in implementing policies. The headmaster has made several important efforts in supporting the quality assurance of the institution by developing the curriculum, human resources, infrastructure and increasing community participation. In managerial terms, the development of the quality of the institution is supported by good coordination with the academic community and the existence of togetherness in curriculum management and learning. In order for quality assurance to be more effective, the headmaster must periodically evaluate every program that has been implemented. The aim is to measure the level of success and find out the deficiencies of the program being implemented. Furthermore, the headmaster needs to conduct more massive socialization of the institution to the community. This is an effort to increase community participation in efforts to develop the quality of schools in the future.